A influência dos ácidos hexenurônicos no rendimento e na branqueabilidade da polpa kraft - Ventorim, Gustavo [UNESP]; Caraschi, José Cláudio [UNESP]; Colodette, Jorge Luiz; Gomide, Jose Livio (Soc Brasileira Quimica, 2009)
This study investigated the impact of pulp hexenuronic acids (HexAs) content on pulping yield by changing cooking reaction temperature. The bleachability of pulps containing variable amounts of HexAs was also investigated. The cooking at 170 degrees C produced pulp of kappa number, HexAs and screen yield of 16.2, 49.4 mmol/kg and 50.2%, respectively, whereas the cooking at 156 degrees C resulted pulp of kappa 17.0, 61.3 mmol/kg HexAs and 50.8% screened yield. The pulp produced at lower cooking temperature also showed better bleachability as evaluated by the total amount of active chlorine required to achieve 90% ISO. The sequence OAHTD(EP) DD showed the lowest bleaching performance among all.
The influence of hexenuronic acids in yield and bleachability of pulp kraft
Keywords: hexenuronic acid; pulping kraft; ECF bleaching